Disciplines of Industrialisation. On the “Scattered” Sztafeta (Relay) by Melchior Wańkowicz - Tomczok, Paweł (Porównania, 2025)
The article presents analyses of the discourse of economic history in the reportage "Relay. A Book about the Polish Economic March" (1939). The most important subject of the book is the significant investment of interwar Poland, namely the Central Industrial Region, located in the middle part of the country, far from the borders, where the production of key materials and goods during the war was to function safely. The discourse on the economic march mentioned in the title is full of enthusiasm reminiscent of the propaganda of the totalitarian states. The fascination with heavy industry and the latest achievements of the chemical industry come to the fore. The article also presents the connections between this discourse and the books by Anton Zischka and other authors popular in the 1930s, proclaiming the need to prepare the country for war by achieving economic autarky. Wańkowicz's book vacillates between fascination with the successes of totalitarian states preparing for the coming wars and attachment to Polish freedom.